Evaluation of the New York City Police Department Firearm Training and Firearm-Discharge Review Process - Rostker, Bernard D. (RAND Corporation, 2008)
In January 2007, New York City Police Commissioner Raymond W. Kelly asked the RAND Corporation to examine the quality and completeness of the New York City Police Department's firearm-training program and identify potential improvements in it and in the police department's firearm-discharge review process. This monograph reports the observations, findings, and recommendations of that study.